2007
DOI: 10.1007/s00294-007-0120-7
|View full text |Cite
|
Sign up to set email alerts
|

RNR4 mutant alleles pso3-1 and rnr4Δ block induced mutation in Saccharomyces cerevisiae

Abstract: The PSO3 gene of Saccharomyces cerevisiae was molecularly cloned by complementing the cold-sensitivity phenotype of a pso3-1 mutant and was found to be allelic to RNR4, encoding one of the two DNA damage-inducible small subunits of the ribonucleotide reductase (RNR) complex. Compared to a rnr4Delta mutant that allows only very little mutation induction at very low doses of 254(nm) ultraviolet light (UVC), the pso3-1 mutant allele confers leakiness in that it permits some DNA damage-induced mutagenesis at low d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…These data suggest that the effect on induced mutation may be generalized to other subunits of the RNR complex. We also demonstrated that RNR4 is required for UV-and MMS-induced increases in dNTP levels, consistent with the ability of the protein to stimulate TLS as proposed previously [38]. Moreover, our data suggest that RNR4 functions in a previously unknown second pathway of induced mutation that involves TLS by the replicative polymerase Polδ.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These data suggest that the effect on induced mutation may be generalized to other subunits of the RNR complex. We also demonstrated that RNR4 is required for UV-and MMS-induced increases in dNTP levels, consistent with the ability of the protein to stimulate TLS as proposed previously [38]. Moreover, our data suggest that RNR4 functions in a previously unknown second pathway of induced mutation that involves TLS by the replicative polymerase Polδ.…”
Section: Discussionsupporting
confidence: 90%
“…Previously, Brendel and co-workers demonstrated that deletion of RNR4 reduces UV-induced mutation and the authors suggested that this resulted from reduced translesion synthesis by Polζ [38]. We first examined the UV sensitivity and mutability of a rad1Δ rnr4Δ mutant to determine whether Rnr4 is involved in NER, the primary repair mechanism responsible for removing UV-lesions.…”
Section: Genes Involved In Induced Mutationmentioning
confidence: 99%
“…The lower processivity of RNR in an rnr4Δ mutant (Y1Y3Y2Y2) that is due to the replacement of the small subunit heterodimer Y2Y4 by the homodimer Y2Y2 leaves the cell with significantly lower-than-normal dNTP pools (Perlstein et al, 2005). These nonadequate dNTP pools lead to somewhat slower cell growth and to significantly increased UVC sensitivity apparently by not allowing efficient repair of DNA damage in rnr4Δ (Strauss et al, 2007) and in the mutant harboring the leaky RNR4 mutant allele pso3-1 Cassier et al, 1980;Brendel et al, 1998). The observed sensitivity to SnCl 2 of the mutant rnr4Δ may thus reflect the (partial) loss of capacity to repair DNA damage.…”
Section: Resultsmentioning
confidence: 99%
“…Imbalanced dNTP pools with one (Brendel, 1985) or all (Chabes et al, 2003) dNTPs at higher-than-normal concentrations lead to increased mutation rates, while an rnr4Δ mutant with a Y2Y2 small subunit homodimer that contains 15 times less diferric-tyrosyl radical co-factor (Perlstein et al, 2005) and apparently lower dNTP pools exhibits slow growth, increased mutagen sensitivity and lower induced mutagenesis (Strauss et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation